The use of 3D body scanning technology to assess the effectiveness of shapewear: changes in body shape and attractiveness. Issue 2 (4th May 2017) - Zhang, Ling; Shin, Eonyou; Hwang, Chanmi; Baytar, Fatma
ABSTRACT: This study investigated the effectiveness of shapewear by examining changes in body shape (CBS) and waist-to-hip ratio (WHR) using 3D body scanning technologies and by exploring an understanding of individuals' perceived body shape and body attractiveness. Using a mixed methods research design, a total of 24 female respondents participated in one of two sessions: quantitative session ( n = 13) and follow-up qualitative session ( n = 11). The results showed that measured CBS were inconsistent with the perceived CBS: a majority of the participants perceived CBS because wearing a shapewear helped them get closer to an hourglass shape and become straighter in the posture, which were not corresponding to the body measurements. Furthermore, significantly lower WHR was partially consistent to perceived attractiveness in general. However, a few participants perceived their bodies as more attractive although their WHR were not changed or even increased.